Cross-sectional properties of the lower limb long bones in the Middle Pleistocene Sima de los Huesos sample (Sierra de Atapuerca, Spain). Issue 117 (April 2018) - Rodríguez, Laura; Carretero, José Miguel; García-González, Rebeca; Arsuaga, Juan Luis
Abstract: The recovery to date of three complete and five partial femora, seven complete tibiae, and four complete fibulae from the Atapuerca Sima de los Huesos site provides an opportunity to analyze the biomechanical cross-sectional properties in this Middle Pleistocene population and to compare them with those of other fossil hominins and recent modern humans. We have performed direct comparisons of the cross-sectional geometric parameters and reduced major axis (RMA) regression lines among different samples. We have determined that Atapuerca Sima de los Huesos (SH) fossils have significantly thicker cortices than those of recent modern humans for the three leg bones at all diaphyseal levels, except that of the femur at 35% of biomechanical length. The SH bones are similar to those of Neandertals and Middle Pleistocene humans and different from Homo sapiens in their diaphyseal cross-sectional shape and strength parameters. When standardized by estimated body size, both the SH and Neandertal leg bones have in general greater strength than those of H. sapiens from the early modern (EMH), Upper Paleolithic (UP), and recent populations (RH). The Sima de los Huesos human leg bones have, in general terms, an ancestral pattern similar to that of Pleistocene humans and differing from H. sapiens .